Análisis de la obra lojanito del compositor “Salvador Bustamante Celi”, adaptación y arreglo para quinteto de cuerdas y contrabajo solista - Torres Paz, Pablo Andrés (2022)
The city of Loja has to its credit an interesting musical history that accounts for the worth of its composers who in one way or another have contributed to the cultural legacy of this emblematic city. The compositions cover a variety of musical genres, but many of them are unknown, so their diffusion and preservation are put at risk. Several musical characters are part of the compositional development of the city of Loja, but without a doubt, the most important is Salvador Bustamante Celi. The objective of this project was to analyze the Lojanito work in its form, structure, and style, to better understand what happens inside the work to propose the arrangement without decontextualizing it. The search for the material was carried out at the "Salvador Bustamante Celi" College of Arts and the "Salvador Zaragocin Tapia" Music Museum, achieving in the latter locating the work understudy, an orchestral arrangement by maestro Julio Bueno. Unfortunately, the original score could not be located. Once the work was located, it was transcribed with the support of Finale musical notation software, and then proceeded to arrange for string quintet and solo double bass.